Effect of Integrated TOGA-Nutrition Education on Stunting Prevention Knowledge among Health Volunteers and Adolescents in Lamongan, Indonesia: A Pre-Post Intervention Study - Idha Kusumawati; Hanni Prihhastuti Puspitasari; Pratiwi Soesilawati; Zamrotul Izzah; Anisa Lailatul Fitria; Firmansyah Ardian Ramadhani; Subhan Rullyansyah; Yusuf Alif Pratama; Charlyna Veronika Puspitasari Pattymahu; Fahmi Haitsami Ibnu Gamar; Ruzainah Ali (Universitas Airlangga, 2025)
Background: Lamongan, Indonesia, is facing a significant public health issue, with high rates of stunting (27.5% in 2022) and adolescent anemia (60.0% in Babat district). A significant knowledge gap exists in the community, particularly regarding the effective use of Family Medicinal Plants (TOGA) for prevention, highlighting the need for structured intervention programs to address these public health issues. This study evaluated an integrated education program designed to improve knowledge and shift perceptions regarding TOGA, assessing differential knowledge gains between health volunteers and adolescents. Methods: This pre-post intervention study involved 54 female participants (27 health volunteers and 27 adolescents) from Kebalanpelang Village, Babat District, Lamongan. All participants received the same 120-minute integrated TOGA-nutrition education based on Social Cognitive Theory, covering stunting prevention, complementary feeding, breastfeeding optimization, and TOGA applications using evidence-based traditional medicinal plants. Knowledge was assessed using the same validated 10-item questionnaire (Cronbach's α=0.81) for both groups, covering three domains: complementary feeding guidelines (3 items), breastfeeding optimization (3 items), and TOGA applications for stunting prevention (4 items), administered before and immediately after the intervention. Results: The intervention was highly effective, yielding a statistically significant 25.4% mean knowledge gain across all participants (3.6±2.1-point gain, p<0.001). Adolescents showed the most dramatic improvement, achieving a 39.7% knowledge increase (a 4.8-point gain). While health volunteers had a more modest gain of 14.7% (a 2.4-point increase), the intervention successfully narrowed the initial knowledge disparity between the two groups by 57% (reducing the gap from Δ4.2 to Δ1.8 points). Domain-specific analysis revealed significant gains across all areas: complementary feeding (+26.8%), breastfeeding (+26.7%), and TOGA applications (+23.9%, all p<0.001). A strong inverse correlation between age and knowledge gain (r=-0.72, p<0.001) indicated that younger participants, particularly those aged 15-17 years, demonstrated superior learning capacity. Conclusions: The implementation of integrated TOGA-nutrition education significantly enhanced stunting prevention knowledge. This intervention is particularly effective for adolescents, which employs role-specific content, successfully mitigates cultural barriers and leads to a measurable reduction in knowledge equity gaps. Strong evidence of participant confirms the program's cultural fit and operational readiness, making a compelling case for its integration and scaling within Indonesia’s broader stunting prevention efforts.